JURNAL REVIEW : KONSEP KEAMANAAN PERBANKAN DI ERA DIGITAL - Putra Dena Pangestu; Hagi Vander Khan, Ghani Irfan Susanto, Ayub Trisna Mukti, Mochammad Rifan Arkaan, Muhammad Bimo Ferl (ADISAM PUBLISHER, 2024)
Increased use of the internet and smartphones in Indonesia, driven by the development of e- commerce and strong digital transformation efforts at banks, has accelerated the migration towards digital banking services. This is demonstrated by the high adoption of digital technology, especially in terms of digital banking. However, there are no clear standards for how well digital banking app users are aware of the security of their data. The aim of this study is to evaluate the level of awareness that digital banking service users have regarding the security of their data to prevent social engineering incidents. In this research, the Knowledge- Attitude-Behavior (KAB) model is used in the Questionnaire of Human Aspects of Information Security (HAIS-Q), as well as a nomenclature for understanding cellular customer information security. The data was combined through a questionnaire distributed to 299 people who met the requirements as respondents. The research results show that digital banking application users in Indonesia have quite good information security awareness, with a score of 81.30% in the knowledge dimension, 84.45% (good), attitude 84.68% (good), and behavior 78.06 % (Enough). Based on these findings, to reduce the threat of social engineering, it is recommended to strengthen regulations relating to the installation of illegal applications and increase awareness training materials on data security. Overall, this study succeeded in testing the level of understanding of digital banking application users in Indonesia regarding the security of their data, with a final score of 81.30%.